2016
DOI: 10.1111/phen.12180
|View full text |Cite
|
Sign up to set email alerts
|

Antennal mechanosensors mediate sex pheromone‐induced upwind orientation in the potato tuberworm moth

Abstract: Males of the potato tuberworm moth Phthorimaea operculella (Lepidoptera: Gelechiidae) locate conspecific females by a series of short and straight flights, or ‘hops’. On the floor of a wind tunnel, P. operculella can change their heading angles in response to wind direction shift, suggesting that they detect wind direction and orient upwind when on the ground. It is unlikely that they navigate in wind by vision‐induced optomotor anemotaxis as in many flying moths. To investigate the mechanism of wind direction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…The addition of PTM1 reduced the time male moths spent near the pheromone source and the pheromone itself compared to PTM2 alone, also increasing the average number of visits to the source; and male potato tuber moths were also found to have behavioral responses to a mixture of PTM1 and PTM2 (1:1) similar to those elicited by the female crude extract. From 1972 to 2016, Ono (1993) ; Ono (1994) ; Ono et al (1997) ; Ono and Orita (1986) and Tejima et al (2013) ; Tejima et al (2016) carried out systematic research on the structure and properties of potato tuber moth sex pheromones. In 1986, they found that the ratio of the sex pheromones was affected by temperature.…”
Section: Field Application Of Potato Tuber Moth Sex Pheromonementioning
confidence: 99%
“…The addition of PTM1 reduced the time male moths spent near the pheromone source and the pheromone itself compared to PTM2 alone, also increasing the average number of visits to the source; and male potato tuber moths were also found to have behavioral responses to a mixture of PTM1 and PTM2 (1:1) similar to those elicited by the female crude extract. From 1972 to 2016, Ono (1993) ; Ono (1994) ; Ono et al (1997) ; Ono and Orita (1986) and Tejima et al (2013) ; Tejima et al (2016) carried out systematic research on the structure and properties of potato tuber moth sex pheromones. In 1986, they found that the ratio of the sex pheromones was affected by temperature.…”
Section: Field Application Of Potato Tuber Moth Sex Pheromonementioning
confidence: 99%
“…To increase the probability of reencountering a lost odor plume, animals orienting upwind typically zigzag across the wind line, and use optic flow to estimate net displacement relative to the ground 2 . Mechanosensory cues appear to contribute to dynamic body control during flight 3 , and even to orientation in specific instances 4 . Thus, animals navigating in a changing flow must sample and integrate chemical, visual and mechanical information, and do so swiftly in order to generate the necessary locomotor responses that will direct them towards an odor source.…”
Section: Introductionmentioning
confidence: 99%